Optimalisasi Dengan Metode Reliability Centered Maintenance (RCM) dan Reliability Centered Spares (RCS) - Fajar Gustian; Asep Endih Nurhidayat (Jurnal Indonesia Sosial Sains, 2022)
Disasters are a series of events that threaten and disrupt people's lives and livelihoods caused by both natural and non-natural and human factors, resulting in human casualties, environmental damage, property losses and psychological impacts. From the losses caused, alertness is needed in order to reduce the side effects that will occur. The social service is one of the government institutions that has an important role in being involved in the distribution of social assistance needed by disaster-affected communities. This role is also a form of alertness carried out by the Social Service in the implementation of disaster response. South Sulawesi Province is one of the large provinces with a high level of fire potential. This study examines the role and efforts of the social services of the South Sulawesi province in disaster response to overcome problems that occur in disaster-affected communities, for example by providing logistical assistance in the form of fulfilling needs that are lacking such as fast food, temporary tents, and the needs of women and children. This study was studied using descriptive qualitative research methods in its preparation in producing conclusions.